NF2 & Gorlins - Evans, D. Gareth R. (Henry Stewart Talks, 2014)
NF2, An autosomal dominant inherited tumours predisposition syndrome, Bilateral vestibular schwannomas, Schwannomas of other cranial and spinal nerve routes, Meningiomas-Ependymomas affected mainly the upper spine, Cataracts, Mutations in the NF2 gene Gorlin syndrome, An autosomal dominant inherited tumours predisposition syndrome, Multiple BCCs, Jaw keratocysts, Medulloblastoma, Mutations in the PTCH gene
Archived at 2024/03/31